Geologia, petrografia e geocronologia das rochas encaixantes do granito Paleoproterozóico seringa, sudeste do do cráton amazônico (Província Carajás) - SANTOS, Max de Jesus Pereira dos (2019)
The Rio Maria Granite-Greenstone Terrane, in which is located the study area, is located in the southeast of the Amazonian Craton, domain of the Amazonian Central Province or, more recently, Carajás Province divided in the Rio Maria and Carajás blocks. Geological mapping, petrographic studies, including mineral chemical by SEM-EDS, and Geochronologic dating in host rocks of the Seringa Granite, Água Azul do Norte and Ourilândia do Norte region, led to identification of distinct TTG rocks. In the northern part of the work area were identified granodioritic rocks containing biotite and amphibole, with NW-SE structural pattern, mineralogical and petrographically similar to the Archean Sanukitoid Rio Maria granodiorite, beyond porphyry biotite granodiorites similar to the biotite granodiorites of the Xingu Complex that outcrop in the northeast, outside of the boundary of the area. In the northeast and southeast portions of the study area occur, respectively, trondhjemite rocks correlated to the Mogno Trondhjemite and potassic leucogranite with similar characteristics to the Xinguara Leucogranite. SEM-EDS semi-quantitative analysis were important in the comparative studies between the rocks of this study and other TTG units of the RMGGT. Biotite, amphibole and zircons from granodiorites of the northeast part of the area are similar to those from Sanukitoid rocks of Rio Maria. Similarly, biotite and zircons from porphyry granodiorite are compositionally similar to those from granodiorites of the Xingu Complex. This fact suggests the existence of distinct granodiorite rocks as host rocks in the northern part of the Seringa Granite. Geochronological dating by Pb evaporation in zircon crystals yielded ages of 2885±Ma for biotite granodiorites of the north portion, and 2874±25 Ma for potassic leucogranites of the southeastern portion of the study area. However, the high 204pb/206pb ratios or the low contents of Pb of most analyzed zircons, together with the few crystals used for the calculation of the average ages of these rocks, allow us to consider these ages as preliminary, but close to the ages of its correlated rocks. Geochronological Laser-Ablation ICP-MS are necessary to define these units.